Multivalued Fixed Point Theorems for Generalized Contractions and Their Applications - Muhammad Shoaib; Muhammad Sarwar (Journal of Mathematics)
We give common hybrid fixed point results for generalized (ψ,ϕ) weak contraction satisfying owc and CLR properties in the framework of metric spaces. An application to functional equations is also discussed.